THE CONCEPT OF ALTERNATIVE EDUCATION AND THE FRAMEWORK OF ITS CRITERIA - Černiauskaitė, Nomeda (Acta Paedagogica Vilnensia, 2012)
The article presents a specified concept of alternative education, since it may represent a wide variety of aspects and depend on the goals set up by an alternative school as well as on the environment where this school functions. Each concept of alternative education reveals the criteria of alternative education in its specific way. These criteria may serve as a basis for modelling an alternative school together with the system of education applied in it, which is able to satisfy most varied learners’ teaching/learning needs in a school of general education, or they may generate an impulse for changes in general education schools. Currently, the demand for an alternative (self-)education emerges: a particular variety of teaching/learning methods allows adapting to individual needs of each learner and provides a possibility of gaining basic or secondary education for individuals who are unable to do it in schools of traditional education. Generalising the concept of alternative education, an emphasis is laid on the meaning of the term “alternative”, i.e. a possibility of free choice. Therefore, alternative education may be referred to as an aggregate of its characteristic features (philosophy of education, methodological approach, principles of organising work, additional services provided, and others), which embodies a paradigm of free education. The most essential criteria of alternative school include specific aims of education, school students from target groups, the content of education, which integrates school students’ personal experience, and various additional services. These criteria have an influence on the motivation of learning/teaching among school students of an alternative school, on the quality of (self-)education; also, they address the requirements imposed by contemporary society. A variety of alternative education criteria results in availability of a broad range of types of alternative schools; therefore, the definition of alterative school is hardly possible without determining its criteria. A specific alternative school may be defined through several essential criteria characteristic of all alternative schools, supplementing this list by features typical only of this particular education institution.